Digital Engineering Learning with Computer Assisted Instruction (CAI) Method - Nainggolan, Irpan (Cattleya Darmaya Fortuna, 2021)
Digital engineering is one of the subjects taught at STMIK Budidarma Medan, where one of the materials discussed is logic gates. The learning process still uses the lecture method, namely delivering the material orally accompanied by the division of tasks and exercises. The absence of simulation is a problem for lecturers in delivering material. Computer Assisted Instruction (CAI) is a learning method that uses computers as a tool to support the teaching and learning process. This method has learning models such as: tutorials, exercises, simulations, and games. With the application of this method, the learning process becomes varied and attracts the attention of students. Based on that.